Berberine in combination with cisplatin induces necroptosis and apoptosis in ovarian cancer cells - Liu, Li; Fan, Jingyan; Ai, Guihai; Liu, Jie; Luo, Ning; Li, Caixia; Cheng, Zhongping (Biological research, 2019)
Berberine (BBR), a compound extracted from a variety of medicinal herbs, has been shown multiple pharmacological effects against cancer cells of different origins. Cisplatin (DDP) is known as an effective chemotherapeutic agent against cancer by inducing DNA damage and cell apoptosis. However, the effect of the combined used of BBR and DDP on cell necroptosis in ovarian cancer has not been reported. OVCAR3 and three patient-derived primary ovarian cancer cell lines (POCCLs) were chosen as the experimental objects. To determine the potential anti-cancer activity of BBR and DDP in combination, we firstly treated OVCAR3 and POCCLs cells with BBR and/or DDP. The cell viability of OVCAR3 and POCCLs with treatment of BBR or DDP for different hours was measured by CCK-8 assay. Flow cytometry was used to analyze cell cycle distribution and changes in apoptotic cells after treatment with BBR and/or DDP. The morphological changes of OVCAR3 cells were observed by using Transmission electron microscopy (TEM) analysis. Proliferation, apoptosis and necroptosis related markers of OVCAR3 and POCCLs with treatment of BBR or DDP were measured by RT-qPCR, western blotting and immunofluorescence assay. Our results demonstrated that BBR significantly inhibited the proliferation of OVCAR3 and primary ovarian cancer cells in a dose- and time-dependent manner. The combination treatment of BBR and DDP had a prominent inhibitory effect on cancer cell growth and induced G0/G1 cell cycle arrest. TEM revealed that the majority of cells after BBR or DDP treatment had an increasing tendency of typical apoptotic and necrotic cell death morphology. Besides, BBR and DDP inhibited the expression of PCNA and Ki67 and enhanced the expression and activation of Caspase-3, Caspase-8, RIPK3 and MLKL. This study proposed that the combination therapy of BBR and DDP markedly enhanced more ovarian cancer cell death by inducing apoptosis and necroptosis, which may improve the anticancer effect of chemotherapy drugs. The apoptosis involved the caspase-dependent pathway, while the necroptosis involved the activation of the RIPK3-MLKL pathway. We hope our findings might provide a new insight for the potential of BBR as a therapeutic agent in the treatment of ovarian cancer.